Ethical and responsive use of artificial intelligence in academic writing and publishing - Subedi, Madhusudan (Journal of Patan Academy of Health Sciences, 2025)
Generative artificial intelligence (AI) has rapidly evolved from novelty to a mainstream driving force in academic writing and scholarly publishing. These tools have become more conveniently accessed and utilized by scholars.1 AI is now directly used in generating text, synthesizing literature, refining grammar, and even proposing novel research directions. These capabilities offer extraordinary opportunities for enhancing productivity, broadening access, and supporting multilingual scholarship.2